What prognostic information does flow cytometry provide in canine B-cell lymphoma? - Haythornthwaite, Benjamin (Veterinary Evidence, 2022)
PICO question In dogs with B-cell lymphoma, does the use of flow cytometry provide useful prognostic information? Clinical bottom line Category of research question Prognosis The number and type of study designs reviewed Twelve papers were critically reviewed. All were cohort studies Strength of evidence Moderate Outcomes reported There are multiple potential prognostic indicators in canine B-cell lymphoma that flow cytometry can be used to evaluate, including lymphoma stage, survival time and time to progression. There is promising evidence for the use of percentage expression of CD25 and Ki67 cellular markers in providing prognostic information in canine B-cell lymphoma and these should be assessed further in clinical practice. Flow cytometry has also been shown to be useful in assessing bone marrow infiltration and providing prognostic information relating to this. There is also evidence for the prognostic value of measuring expression of class II MHC and CTLA-4 cellular markers, peripheral lymphocyte / monocyte ratio, nodal regulatory T-cell populations and the ratio between T and B lymphocytes in extranodal locations. Peripheral regulatory T-cell populations and cellular size were also assessed, however further investigations are required before confirming their prognostic value Conclusion Flow cytometric analysis offers useful measures of prognosis in canine B-cell lymphoma, although further validation is required before introducing their routine use. Percentage expression of CD25 and Ki67 cellular markers from lymph node aspirates of dogs with B-cell lymphoma appear to be promising prognostic indicators in clinical investigations, however this needs to be translated into clinical practice. While there is evidence for the prognostic value of bone marrow infiltration measured flow cytometrically, expression of class II MHC and CTLA-4, peripheral lymphocyte / monocyte ratio, nodal regulatory T-cell populations and the ratio between T and B lymphocytes in extranodal locations, these need to be further investigated before introducing into clinical practice. As new antibodies against cellular targets in dogs become available, it is likely that flow cytometry will become even more useful in providing prognostic information How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.